THE INFLUENCE OF LEARNING MODEL COOPERATIVE TYPE GROUP INVESTIGATION (GI) ON STUDENT STUDY RESULT ON LEARNING MATERIAL THE MAINTENANCE OF GASOLINE FUEL SYSTEM COMPONENT IN GRADE XI MOTORCYCLE ENGINEERING SMK NEGERI 1 PALANGKA RAYA ACADEMIC YEAR 2014/2015 - Feriyanto; Jhonni Rentas Duling (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2015)
The purpose of this study was to determine whether there is an influence between the learning outcomes of students who were taught by lecturing on the subjects of gasoline fuel system in class XI SMK 1 Palangkaraya. This study used two different classes that involved 32 students of class XI TKR (Light Vehicle Engineering) SMK 1 Palangkaraya are divided into two classes, namely, class XI TKR 1 with 16 people and the number of students in class XI TKR 2, amounting to 16 people, and the type of research is experimental. In this study the instrument in the form of a multiple choice test to collect data of student learning outcomes. Data were analyzed with normality test, homogeneity test and t-test, normality test for pre-test experimental class X2calculated<X2table, is 3.859 <9.488, test of normality to pre-test the control class X2calculated<X2table, namely 3.178 <9.488, while for normality teston post test of experimental class X2calculated<X2table, namely 3.846 <9.488, normality test of post test of control class X2calculated<X2table, namely 3.011 <9.488, test of homogeneity obtained Fcalculated = 1.01 < Ftable = 2.31 otherwise homogeneous. T-test obtained tcalculated = 10.51> ttable = 2.042, so there is an influence on student learning outcomes taught using learning model-type Group Investigation (GI) on the material maintenance of gasoline fuel system components in class XI TKR (Light Vehicle Engineering) SMK Negeri 1 Palangka Raya academic year 2014/2015.